BERLATIH RAGAM APLIKASI PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 - Tri Astuti Arigiyati; Betty Kusumaningrum; Krida Singgih Kuncoro; Muhammad Tri Wijaya; Taufik Hidayat (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2021)
The Covid-19 virus spreads very quickly to various countries in the world. Various efforts have been made to break the chain of spreading the Covid-19 virus, one of which is by changing face-to-face learning methods into online learning. The obstacles that are students at the Madania Modern Yatim and Dhu'afa Islamic Boarding School Foundation (YPPMYD) during online learning are the low motivation to learn and the lack of knowledge of online learning resources. The solution to the problems offered by community service activities is training and assisting the installation of online learning application and how to use them. This service activity was carried out in a bold and attractive manner. Online it was done using the Google Meet application, while offline it was conducted at the Madania Bantul Yogyakarta Modern Yatim Islamic Boarding School Foundation (YPPMYD), which was attended by 12 students and 2 companions from students. At the end of the activity, students came to fill out a questionnaire. The results of the questionnaire showed an increase in student learning motivation by 91.07%, an increase in independence by 86.98% and an increase in knowledge of learning applications by 90%.